Vaccinating and non-vaccinating parents' attitudes toward influenza vaccination in children under 5 years old in Spain - Zornoza-Moreno, Matilde; Sánchez-Manresa, Susana; Gómez-Moreno, María Cruz; Ros Abellán, María Pilar; Pérez-Martín, Jaime J. (Frontiers in Public Health, 2025)
BackgroundVaccines against seasonal influenza represent the best option to reduce the cases and severity of the disease in children under 5 years. In Spain, the Region of Murcia was a pioneer in implementing universal vaccination at schools. The study aimed to evaluate the acceptance and attitudes of parents of children of 6–59 months old toward influenza vaccination and factors associated with parents' decision to vaccinate their children during the 2023–2024 campaign.MethodsThis prospective, descriptive study used a questionnaire to collect data from parents of vaccinated (VC) and non-vaccinated children (nVC). VC received either the live-attenuated intranasal vaccine (LAIV) or the intramuscular vaccine (IIV) depending on their age.ResultsParent's self-vaccination/intention in this campaign (OR: 8.51) and in the previous one (OR: 4.49), and children's compliance with vaccination schedule (OR: 7.83) were the main factors associated with the probability of children being vaccinated against influenza. The main reason for vaccinating was to protect the child (IIV: 92.5% vs. LAIV: 91.0%), while waiting for further experience with the vaccine (21.0%) and lack of recommendation from the healthcare professional (20.4%) were the major reasons for not vaccinating. Most vaccinating parents (IIV: 90.4% vs. LAIV: 93.9%, p < 0.001) were satisfied with the vaccine. Among VC at school, 95.8% of parents were satisfied and 97.4% would recommend for family and friends.ConclusionsParents of VC, especially those vaccinated with LAIV at schools, were highly satisfied with the vaccine. Parent's influenza vaccination status and children's compliance with vaccination schedule were determinant for parent's decision to vaccinate children under 5 years old. More information about influenza vaccination could help increase vaccination rates in these children.